Likely to die - Fairstein, Linda A. (Fairstein, Linda A. Alexandra Cooper novels., 1997)
A neurosurgeon is sexually assaulted, stabbed and left for dead in her office at the labyrinthine Mid-Manhattan Medical Centre. The police designate her Likely to Die. Alexandra Cooper, head of the district's sex crimes unit, assembles a task force to investigate but finds herself hindered at every turn. Not only has her office prosecuted some of the vast hospital's patients and staff before but the building itself compounds the problem. A vast complex encompassing a medical college and the Stuyvesant Psychiatric Centre, the hospital rises over a network of tunnels now occupied by numberless transients who have easy access to the corridors. Strung out with other cases and mired in the investigation personally when even the man she has begun to date, has a connection to the case, Alex must find the killer - before the killer finds her.....